Os jornais, a democracia e a ditadura do mercado: a corbetura das eleições presidenciais de 2002 - Nassif, Maria Inês (2007)
The paper intends to show, by surveying the period immediately before Brazil´s presidential elections in 2002, how O Estado de S. Paulo and Folha de S. Paulo, two major newspapers printed in the country s major financial center, performed as mediators of the pressure applied by the financial markets upon voters and contenders, particularly upon the Worker s Party candidate, Luiz Inácio Lula da Silva. A feedback circuit between news and markets inserted the newspapers in the process of financial capital accumulation. São Paulo´s newspapers undertook the function of organic intelectuals in the electoral process and acted in a very organic way, assumedly as ideological private apparatuses, like political parties